2006
DOI: 10.1196/annals.1373.059
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Babesiosis Live Vaccine Production

Abstract: Gamma irradiation on bovine serum and red blood cells (RBC) allows proliferation and growth of in vitro-cultured Babesia sp., and has potential application to inactivate contaminating viruses and bacteria from the substrate. Gamma irradiation with 25 kGy in a source of (60)Co was able to inactivate infectious bovine rinotracheitis (IBR) and bovine viral diarrhea (BVD) viruses in artificially contaminated serum; besides, bacteria were also eliminated. In vitro culture of Babesia bovis (B. bovis) in modified sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Gamma irradiation of serum inactivates the viruses of foot and mouth disease, vesicular stomatitis, rinderpest, peste des petits ruminants, Rift Valley fever, and bluetongue while maintaining growth promotion potential. Attenuated vaccines for B. bovis and B. bigemina (Rojas et al 2006) require regular supplies of bovine red blood cells (RBCs) and serum for their manufacture, and there is a constant problem with contaminating viruses and bacteria. Irradiation of serum with 25,000 Gy has therefore been used to inactivate viral contaminants and ensure its safety and efficacy in use.…”
Section: Introductionmentioning
confidence: 99%
“…Gamma irradiation of serum inactivates the viruses of foot and mouth disease, vesicular stomatitis, rinderpest, peste des petits ruminants, Rift Valley fever, and bluetongue while maintaining growth promotion potential. Attenuated vaccines for B. bovis and B. bigemina (Rojas et al 2006) require regular supplies of bovine red blood cells (RBCs) and serum for their manufacture, and there is a constant problem with contaminating viruses and bacteria. Irradiation of serum with 25,000 Gy has therefore been used to inactivate viral contaminants and ensure its safety and efficacy in use.…”
Section: Introductionmentioning
confidence: 99%
“…Some drawbacks for the use of attenuated vaccines have been described that include the spread of adventitious pathogens, difficulties in dose standardization, parasite virulence reversion and quality control stringencies during the production and handling of the vaccines. However, vaccines containing in vitro culture-derived parasites are processed under more controlled conditions, and have a lower risk to acquire adventitious pathogens due to gamma radiation of the serum, and more recently by using bovine serum-free culture medium ( 31 , 36 , 91 , 93 ). As for the handling of the vaccine inoculum, the usefulness of the vaccine as fresh or frozen material has been demonstrated ( 35 , 119 ).…”
Section: Experiences On Live Attenuated Vaccines From Other Countriesmentioning
confidence: 99%
“…At about the same time, the in vitro cultivation of Babesia was developed, a system from which attenuated strains that have functional immunogenic proprieties have been derived and tested. These strains have been used both in controlled and field studies, in which protection in vaccinated cattle of at least 80% has been demonstrated when challenged with virulent strains (33)(34)(35)(36).…”
Section: Control Of Bovine Babesiosis With the Use Of Immunogensmentioning
confidence: 99%
“…Several attempts over the past decade have been made to develop an anti‐ Babesia vaccine; however, no vaccine has yet proven to be completely effective in preventing the infection (2,12). Live attenuated vaccines derived from blood are believed to induce long‐lasting immunity, but their use has disadvantages such as difficulties in standardization of vaccine dose, short shelf‐life and risk of reversion of virulence (13,14). Soluble parasite antigens derived from different Babesia species have been proven to induce immune responses that reduce manifestations of clinical disease upon infection, but cannot prevent infection (15,16).…”
Section: Introductionmentioning
confidence: 99%